2020
DOI: 10.3390/app10248901
|View full text |Cite
|
Sign up to set email alerts
|

Retained Austenite Destabilization during Tempering of Low-Temperature Bainite

Abstract: The thermal stability of nanostructured microstructures consisting of a mixture of bainitic ferrite and carbon-enriched retained austenite has been studied in two steels containing 0.6 C (wt %) by tempering cycles of 1 h at temperatures ranging from 450 to 650 °C. Volume changes due to microstructural transformations during thermal treatments were measured by high-resolution dilatometry. The correlation of these results with the detailed microstructural characterization performed by X-ray diffraction and scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…III). This con rm degradation of the microstructure during annealing at higher temperature -carbides precipitation and retained austenite transformation [14,17] . On the basis of dilatometric and mechanical tests the temperature of low temperature glow discharge nitriding was selected at 420°C.…”
Section: Simulation Of Nitriding Processes In Dilatometric Testsmentioning
confidence: 57%
“…III). This con rm degradation of the microstructure during annealing at higher temperature -carbides precipitation and retained austenite transformation [14,17] . On the basis of dilatometric and mechanical tests the temperature of low temperature glow discharge nitriding was selected at 420°C.…”
Section: Simulation Of Nitriding Processes In Dilatometric Testsmentioning
confidence: 57%
“…Thus, the de-composition mechanisms should be comparable to the tempering processes. Retained austenite during tempering decomposes into a mixture of cementite and ferrite (γ R → α + θ ) [21]. There Austenite decomposition products may also be pearlite [22], martensite (induced transformation of retained austenite [23]), and bainite [24].…”
Section: Resultsmentioning
confidence: 99%
“…Although Mn is a stabilizer of austenite, it was proposed to reduce its content (0.5 wt.%) and increase the content of Cr (1.5 wt.%) to accelerate bainite transformation and achieve sufficient hardenability. It was stated that V (0.2 wt.%) has a beneficial effect on retarding the decomposition process during tempering [28,29]. Another aspect is also controlling the grain size of the prior austenite, which is significant in terms of steel's susceptibility to grain coarsening.…”
Section: Design Process Of Experimental Steelmentioning
confidence: 99%
“…However, it was observed that the hardness at 550 • C was comparable to the state before tempering. This may be explained by the strengthening effect of fine-dispersed carbide precipitations (related to alloying elements such as Mo and V-secondary hardening), similar to [29,52].…”
Section: Tempering Process-thermal Stability Evaluationmentioning
confidence: 99%